Akayesu: El primer juicio internacional por genocidio Rafael A. Prieto Sanjuán (Director) Sandra P. Ávila González, Ximena Castrillón Ayerbe, Elisa Gutiérrez Baena, Marcela I. Mantilla Martínez. Pontificia Universidad Javeriana, Bogotá y Diké - Olarte Bacarés, Diana Carolina; Pontificia Universidad Javeriana (2007)
null